Self-adaptable mechanical ceramic fibrous aerogels from prestressed topology and multistable constraints - Hongxing Wang; Longdi Cheng; Jianyong Yu; Yang Si (Nature Communications)
Abstract Ceramic aerogels, widely used as thermal insulation materials, are renowned for their remarkable characteristics, including ultralight weight and ultralow thermal conductivity. However, their application is often limited by susceptibility to damage under repeated dynamic thermal shocks—a challenge that remains inadequately addressed. Herein, we present a multicomponent structural engineering approach that integrates ceramic nanofibers with traditional textile knitting topology to fabricate mechanically adaptable ceramic fibrous aerogels. Benefiting from the porous nanofibrous network and the synchronized motion of the prestressed knitted topological framework, which can be readily activated to accommodate deformation while efficiently dissipating energy, the resulting aerogels exhibit exceptional mechanical properties. Specifically, our aerogels demonstrate a high tensile strength of 356.6 kPa, a compressive strength of 109.1 kPa, and remarkable mechanical adaptability in response to external stimuli. Moreover, these aerogels achieve a high fracture energy of 117.26 kJ m-3 and display exceptional recovery from deformation after 1000 cycles of compression or 500 cycles of tension. This study elucidates the structural-property interdependence in aerogel materials through multiscale analysis and advances the rational design of the next-generation impact-absorbing systems and metamaterials.